The High Energy Scattering Amplitude One-loop Gravitation in the Effective Field Theory - Thu Ha, Do; Thu Huong, Nguyen (VNU Journal of Science: Mathematics - Physics, 2023)
In this work, the Newton potential, together with the low-key corrective energy, an attractive loop of two large non-relativistic masses has been found. The asymptotic behavior of the scattering amplitude for two scalar particles at high energies with fixed momentum transfers was studied in the one-loop gravitation effective field theory.